The Influence of a Scientific Approach on the Scientific Attitudes of Students in Class V Science Subjects - Ria Rizki Agustini; Hamdan Hariri; Siti Aisah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The complexity of the difficulties faced in the field of education and teaching is influenced by several factors; one of these elements is the approach to the learning process. This research examines how the scientific process influences students' views of science. Science curriculum part V. This research used a quasi-experimental approach with a non-equivalent control group. SDN 04 In May 2023, Leuwiliang Bogor will become the research location. This research involved 41 VA and 39 VB students. This research uses interviews, questionnaires and notes. Data analysis includes validity, reliability, normality, homogeneity, and testing. Testing the 2-tailed t test hypothesis using SPSS type 25 software obtained data of 0.010 with a significance level of 0.0.05 or significance. Class VB has an average value of 81%, while class VA has an average value of 87%, with 2-tailed) < 0.05. The findings of the analysis test revealed that the scientific learning techniques used in the VA class did have an effect in improving students' attitudes towards science.